Pengaruh Turnover Intention terhadap Kinerja Karyawan di Rumah Sakit Bedah Surabaya - Alfatania Pandu Asmara (Indonesian Journal of Health Administration (Jurnal Administrasi Kesehatan Indonesia), 2017)
The turnover rate of employee in Surabaya Surgical Hospital increased over the last three years since 2014 to 2016 that was 13,67% in 2014, 13,69% in 2015 and 16,91% in 2016. The high employee turnover rate of Surabaya Surgical Hospital was probably due to high turnover intention of employees in some work-units at Surabaya Surgical Hospital on 2016 with the individual average value by 50.80%. The high value of turnover intention could give an impact in employee performance. Holzer, Stoll, and Wissoker (2004) stated that employees would reflect the high turnover intention by not fulfilling the tasks and responsibilities at work. Turnover intention did not only impact the final performance, but also affected employees' commitment to work. This research aimed to analyze the effect of turnover intention on employee performance. The sample of this research was Surabaya Surgical Hospital employees with minimum six months working period. The method of this research was analytical observational study with cross sectional design. The result showed that turnover intention affected the employee performance with the p value or significance was 0.03 and smaller than α = 5% (0.05). It can be concluded that turnover intention has an effect on employee performance.Keywords: turnover intention, work commitment, work performance